Through Their Lenses: A Photovoice Exploration of Online and Home-Based ESL Teachers’ Pitfalls in the Philippines - Ramos, Ariel (Journal of Studies in the English Language, 2025)
Home-based and online English as a second language (ESL) work offers teachers welcome flexibility, but it also brings challenges that can wear them down over time. This study examines how those pressures shape teachers’ professional well-being and day-to-day work through a critical realist lens. Using a photovoice design, 10 home-based ESL teachers from Southern Cebu acted as co-investigators. They documented their experiences through photographs and group discussions guided by the SHOWED framework that represented the questions like what is seen, what is really happening, how it relates to our lives, why it exists, how it educates others, and what can be done. In addition, the visual and verbal data were analyzed to trace patterns shaping their working lives. Five recurring themes emerged: the digital divide, routine risks, income instability, disciplinary distraction, and physiological problems. Together, these themes show how uneven access to technology, long and fragmented workdays, unstable income, student distraction in home settings, and the physical strain of screen-based work intersect in teachers’ lives and affect how they teach. The findings point to the need to support educator resilience and strengthen institutional systems rather than leaving teachers to cope alone. In practical terms, the study invites ESL providers to rethink policies, technological support, workload expectations, and health provisions so they better reflect the everyday realities of home-based online teaching in the Philippine context.